Tetracycline photolysis revisited: Overlooked day-night succession of the parent compound and metabolites in natural surface waters and associated ecotoxicity. (15th October 2022) - Peng, Anping; Wang, Chao; Zhang, Zhanhua; Jin, Xin; Gu, Cheng; Chen, Zeyou
Highlights: Phototransformation of tetracycline and its metabolites under day-night succession was investigated. Unrecognized dark hydrolysis of tetracycline metabolites in natural waters was observed. Isomerized, hydroxylated, demethylated, deaminated, and open-ring products were major tetracycline photoproducts. The dark transformations affect the bacterial toxicity and fluorescence properties of irradiated tetracycline solutions. Abstract: Despite the extensive study of tetracycline photolysis in aquatic environments, the phototransformation of tetracycline and its metabolites under natural day-night succession has not been examined. In this study, we investigated tetracycline photolysis and associated ecotoxicity in two natural surface waters and one artificial ultrapure water under simulated day/night cycling over two days. Previously unrecognized and highly pH- and temperature-dependent dark interconversions of tetracycline metabolites were observed. The liquid chromatography-mass spectrometry/mass spectrometry analysis identified a range of isomerized, hydroxylated, demethylated, deaminated, and open-ring photoproducts. The hydrolysis of tetracycline, isotetracycline, and several intermediate products was proposed as the major mechanism for the observed dark transformations. Exposure studies employing Escherichia coli indicated that although the tetracycline degradation products had lower bacterial toxicities than the parent compound, increasing toxicity with irradiation time after the near-complete degradation of the parent compound in natural waters implied that product mixtures retain ecotoxicity. The dark transformations also affected the bacterial toxicity and fluorescence properties of irradiated tetracycline solutions. Overall, this study provides new insights into the photochemical behavior of tetracycline and its associated ecological risk in aquatic environments. Graphic abstract: Image, graphical abstract